Almost sure stability with general decay rate of neutral stochastic delayed hybrid systems with Lévy noise. (May 2017) - Li, Mengling; Deng, Feiqi
Abstract: This paper focuses on neutral stochastic delayed hybrid systems with Lévy noise (NSDHSs-LN). A kind of ψ -function is introduced and the almost sure stability with general decay rate is investigated, including the exponential stability and the polynomial stability. By virtue of Lyapunov function and nonnegative semi-martingale convergence theorem, we propose sufficient conditions for the almost sure stability of the NSDHSs-LN. Moreover, we give an upper bound of each coefficient at any mode according to the theory of M-matrix. Especially, the coefficients of considered systems can be allowed to be high order nonlinear. Finally, two examples are given to show the effectiveness of our results.